Constitutionalization of Arbitration - S. A. Kurochkin (Ученые записки Казанского университета: Серия Гуманитарные науки, 2024)
The number of arbitration cases handled by the Constitutional Court of the Russian Federation has steadily increased over the years. The evolution of social practices and judicial approaches to arbitration procedures has prompted the supreme body for judicial protection of the Russian Constitution to repeatedly review whether the legal concepts used to resolve civil disputes by arbitration courts and international commercial arbitrations align with the nation’s basic law. The outcome of this process is a set of legal principles that define the constitutional and judicial foundations of arbitration in Russia. The above trends have facilitated the use of the integrative concept of constitutionalism in arbitration. This study highlights the constitutionalization of both arbitration and its social application. From a standalone perspective, the problems of enhancing the constitutional and legal principles of arbitration were discussed, and the further progress of constitutionalism in Russian arbitration was predicted.